A Study on Lalehzar Street to be Changed to a Proper Walking Street While Focusing on Loose Spaces - Safari, Sepideh (ICONARCH International Congress of Architecture and Planning, 2014)
Nowadays, the quality and attraction of public urban spaces has been one of the most crucial features for a city to be called developed and manageable. Pedestrian walkways have a key role in social interactions in todays’ virtual technology age, economical impacts on the areas around and multi-functional dimensions encompassing a wide range of activities. Historical texture and pedestrian walkways have an important role in peoples’ quality of living, therefore, different factors affecting pedestrian walkways should be recognized and the loose spaces should be used as a parameter to develop the pedestrian walkways qualitatively. Having studied the related theories and concepts, and also Lalehzar street which has lost its livelihood, the mentioned theories have been tried to be proven right. This research tries to find strategies to make Lalehzar a successful urban pedestrian walkway. Since the concept of Loose space has not been utilized for similar places in Iran, and it is an effective factor in lively spaces, utilizing it along with historical Lalehzar pedestrian walkway can be considered an innovative approach. Therefore, the research model is prepared which covers the general model affecting factors on practical pavements and proper urban spaces. Furthermore, the loose spaces are used for comparison and, finally, the loose spaces are mentioned as a progressive development factor along with the pedestrian walkways.